Optimization model for consumption taxation in Malaysia: a case study of goods and services tax - Razali, Nurul Farhani (2020)
This thesis describes the development of an optimization model and its application for consumption taxation in Malaysia. Its main idea was to propose the model, which is an individual model, linked together with firm and government behaviours, in the case of taxation in Malaysia, where goods and services tax (GST) is considered. For all the median household income groups of T20, M40, and B40 being studied, the consumption levels for the current and future periods are set to be the decision variables. In the proposed model, the respective utility function was maximized, where the related budget constraints were satisfied. It was highlighted that, some firm behaviours affected the individual’s utility level, while the government consumption covered both individual and firm. The Lagrange multiplier method was applied to solve the proposed model. The first-order necessary conditions for the model were derived and the computational solutions were obtained in the Excel spreadsheet environment, with the consumption tax varied in the range of 5 to 7 percent. The results obtained revealed that, all of the individual’s populations were burdened by the GST implementation, while the government consumption increased. It was also showed that, the appropriate consumption tax rate for the individual and for the government is 5 percent and 7 percent, respectively. Moreover, since there were three situations considered for tax reform, namely, varying the consumption tax rate, cutting the real property gains tax rate and varying the transfers, it is expected that, the Malaysia taxation policy guidelines could be further improved. In conclusion, the optimization model on the consumption taxation in Malaysia was proposed. Besides the Lagrange multiplier method was successfully applied to solve the optimization model. Lastly, the usefulness of the proposed optimization model for Malaysia was successfully validated. The findings of this study could be used to provide a useful guideline for setting the Malaysian consumption taxation policy in the future.